The relationship between different types of co-speech gestures and L2 speech performance - Ma, Sai; Jin, Guangsa (Frontiers in Psychology, 2022)
Co-speech gestures are closely connected to speech, but little attention has been paid to the associations between gesture and L2 speech performance. This study explored the associations between four types of co-speech gestures (namely, iconics, metaphorics, deictics, and beats) and the meaning, form, and discourse dimensions of L2 speech performance. Gesture and speech data were collected by asking sixty-one lower-intermediate English learners whose first language is Chinese to retell a cartoon clip. Results showed that all the four types of co-speech gestures had positive associations with meaning and discourse L2 speech measures but no association with form-related speech measures, except the positive association between metaphorics and the percentage of error-free clauses. The findings suggest that co-speech gestures may have a tighter connection with meaning construction in producing L2 speech.